2020
DOI: 10.1093/scan/nsaa039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic human and avatar facial expressions elicit differential brain responses

Abstract: Computer-generated characters, so-called avatars, are widely used in advertising, entertainment, human–computer interaction or as research tools to investigate human emotion perception. However, brain responses to avatar and human faces have scarcely been studied to date. As such, it remains unclear whether dynamic facial expressions of avatars evoke different brain responses than dynamic facial expressions of humans. In this study, we designed anthropomorphic avatars animated with motion tracking and tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…On the other hand, Sarkheil et al (2013) concluded that even when using advanced motion tracking and visualization techniques, the artificial facial motion of avatars leads to differences in the activation of these regions when compared to human facial motion. Taken together Kegel et al (2020) concluded, that dynamic avatar expressions evoke fast amygdala responses comparable to those of humans, but the artificial facial motion of those avatars lead to differences in slower cortical process mechanisms.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…On the other hand, Sarkheil et al (2013) concluded that even when using advanced motion tracking and visualization techniques, the artificial facial motion of avatars leads to differences in the activation of these regions when compared to human facial motion. Taken together Kegel et al (2020) concluded, that dynamic avatar expressions evoke fast amygdala responses comparable to those of humans, but the artificial facial motion of those avatars lead to differences in slower cortical process mechanisms.…”
Section: Introductionmentioning
confidence: 81%
“…The same stimuli material was used in a successfully published event-related fMRI work by Kegel et al (2020). This fMRI study aimed to investigate whether there are differences in cortical and subcortical processing mechanisms when comparing human and avatar dynamic facial expressions (Kegel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose this approach to avoid the need to deceive participants into thinking they were playing the game with a real human partner. In prior studies, participants have been found to respond similarly to human and anthropomorphic characters on a behavioral level, but it should be noted that there are indications that responses to human interaction partners on a neural level are stronger than those to andromorphic characters (e.g., Kegel et al, 2020;Riedl et al, 2011). Nevertheless, findings of the current studies are in line with prior Trust Game and social decision-making studies with human partners (e.g., Fett et al, 2014a;Lemmers-Jansen et al, 2017;Lemmers-Jansen et al, 2019;van den Bos et al, 2011;van Hoorn et al, 2019), suggesting that participants perceived the trustee as a human(-like) being.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that perception of emotional expression in human-like characters can be processed similarly to human stimuli. However, Kegel et al [15] showed differences in the perception of fearful dynamic avatars and dynamic human faces. Gender [23], culture [8] and race [11] have been reported to influence FER.…”
Section: Virtual Agents and Emotionsmentioning
confidence: 99%